Bossa Nova: The Reinvention and Reinvigoration of Samba in the 1950s - Helmiawan, Martinus (Paradigma: Jurnal Kajian Budaya, 2013)
In a society where music becomes the core of its people’s life, many discourses emerge and root in music. In Brazil, for instance, samba as the national music represents the chronicle of the Brazilians, which starts from the slavery in eighteenth century. However, at the start of the era of Brazil’s modernism in 1950s, samba was deemed stagnant. It was unable to cope with the fast developments of Brazil’s politics, societies, and cultures. This essay observes the history of samba, investigates the reasons why samba becomes stagnant and reviews the efforts made to revitalize it through the invention of Bossa Nova. In the process of redefining samba, American jazz plays an important role as the agent which brings modernity and revolution to the original samba. The ideology of the Brazilian urban middle class is also important, as well as Brazilian 1950s musicians’ efforts such as Antonio Carlos Jobim, Joao Gilberto, or Vinicius de Moraes. This paper aims to analyze Bossa Nova’s contributions in revitalizing and redefining samba, with its jazz influence which could be traced from the ideology of the Brazilian urban middle class. The paper also highlights the contradiction between foreign influences and traditional heritages in the music.